2022
DOI: 10.3390/diagnostics12081958
|View full text |Cite
|
Sign up to set email alerts
|

FAPI PET versus FDG PET, CT or MRI for Staging Pancreatic-, Gastric- and Cholangiocarcinoma: Systematic Review and Head-to-Head Comparisons of Diagnostic Performances

Abstract: Introduction: There is a pressing demand for the development of cancer-specific diagnostic imaging tools, particularly for staging of pancreatic-, gastric- or cholangiocarcinoma, as current diagnostic imaging techniques, including CT, MRI and PET using FDG, are not fully adequate. The novel PET-tracer “FAPI” has the potential to visualize even small tumour deposits employing the tumour-specific expression of fibroblast-activating protein (FAP) in malignant cells. Methods: We performed a systematic review to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
10
0
2
Order By: Relevance
“…In this case, the relatively novel radiotracer, 68 Ga-labeled FAPI, was successful in assessing primary Klatskin tumor and avoided the well-known false-negative pitfall of the more traditional 18 F-FDG, particularly for the histological mucinous subtype 1,2 . Indeed, this was in line with the expectations of colleagues in the field who have explored the comparable utility of 68 Ga-FAPI PET/CT in the oncologic field generally, as well as for tumors of biliary origin specifically 3–9 . According to Dendl et al, among others, the explanation could be found in the relatively unique tumor microenvironment of the major cholangiocarcinoma subtypes and the associated abundance of desmoplastic reactions and cancer-associated fibroblasts 10,11 .…”
supporting
confidence: 64%
“…In this case, the relatively novel radiotracer, 68 Ga-labeled FAPI, was successful in assessing primary Klatskin tumor and avoided the well-known false-negative pitfall of the more traditional 18 F-FDG, particularly for the histological mucinous subtype 1,2 . Indeed, this was in line with the expectations of colleagues in the field who have explored the comparable utility of 68 Ga-FAPI PET/CT in the oncologic field generally, as well as for tumors of biliary origin specifically 3–9 . According to Dendl et al, among others, the explanation could be found in the relatively unique tumor microenvironment of the major cholangiocarcinoma subtypes and the associated abundance of desmoplastic reactions and cancer-associated fibroblasts 10,11 .…”
supporting
confidence: 64%
“…As management of these subtypes differs, assessing tumor infiltration into the bile duct and surrounding tissues is essential but is often challenging. [7][8][9][10] e-CCA comprises perihilar cholangiocarcinoma (pCCA or Klatskin tumor), the most common form, and distal cholangiocarcinoma (dCCA), which occurs in 50% and 30%-40% of cases, respectively. 11 Globally, the prevalence of ICC has increased substantially by 109% over the last 10 years, from 0.67 per 100 000 in 2007 to 1.40 per 100 000 in 2016.…”
Section: B (Hepatitis B Virus [Hbv]) Chronic Hepatitis C (Hepatitis C...mentioning
confidence: 99%
“…Cholangiocarcinoma (CCA) tumor includes the intrahepatic subtype above the second‐order bile ducts, which typically accounts for 10%–20% of cases, and extrahepatic subtypes (e‐CCA). As management of these subtypes differs, assessing tumor infiltration into the bile duct and surrounding tissues is essential but is often challenging 7–10 . e‐CCA comprises perihilar cholangiocarcinoma (pCCA or Klatskin tumor), the most common form, and distal cholangiocarcinoma (dCCA), which occurs in 50% and 30%–40% of cases, respectively 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from FDG and PSMA, several other tracers are currently being used and investigated in PET imaging, most prominently FAPI, which uses the tumor expression of fibroblast-activating protein (FAP) to diagnose and stage patients with cancers of the stomach or pancreas, and cholangiocarcinoma 210 . Other tracers are 18 F-fluoroethyl-L-tyrosine (FET) and 11 C-methionine (MET), which correlates with microvessel density in proliferating cells, both of which are used in glioma imaging; 68 Ga-DOTATOC (DOTA 0 -Phe 1 -Tyr 3 -octreotide), a somatostatin analog used to detect neuroendocrine tumors 211 ; and 11 C-metomidate PET, which is used to detect adrenal masses 212 .…”
Section: Hybrid Imaging: Positron-emission Tomography Ct and Mrimentioning
confidence: 99%